Overview of the Effect of Complementary Obstetric Care of Guava Juice and the Application of Logbook to Increase Hb Levels - Pisnitri, Pisnitri; Nilawati, Iin; Herlinda, Herlinda; Elly, Nur (Universitas Islam Lamongan, 2022)
Anemia in pregnancy is called